Impacto tecnologico en la trazabilidad de las exportaciones en pequeñas y medianas empresas (pymes) en colombia. (2022)
The purpose of this research is to analyze the impact of technology on the traceability of exports and imports in small and medium-sized enterprises (SMEs) in Colombia, as well as the consequences and effects of not implementing technological tools for the monitoring and control of their foreign trade operations. On the other hand, it indicates the evolution of traceability with technological means, the problems and limitations for its implementation, and the advantages that its use can have for medium, small, and micro enterprises